Do Gender Differences Exist Among Victims of Head and Neck Injuries due to Intimate Partner Violence? - Amin, Dina; Manhan, Andrew J.; Zeidan, Amy J.; Evans, Dabney P.; Abramowicz, Shelly; Smith, Randi N. (Journal of Oral & Maxillofacial Surgery (02782391), 2023)
Purpose: The frequency of intimate partner violence (IPV) is much lower in males than females. Data regarding IPV-related injuries patterns and characteristics in males are scant. The purpose of this study was to characterize and compare patterns of IPV-related head and neck injuries between men and women.Materials and Methods: This cross-sectional study reviewed cases of IPV at Grady Memorial Hospital in Atlanta, Georgia from January 2016 to August 2019. The study sample was collected from electronic medical records by identifying IPV subjects using a natural language processing algorithm and then cross-referencing the trauma registry to identify patients who sustained head and neck injuries. The primary analyses of interest were to measure the association between gender and the following covariates: age, race, insurance status, setting of injury, day of injury, social history, report of physical abuse, mechanism of injury, injury location, brain injuries, soft tissue injuries, facial fractures, other associated injuries, Glasgow Coma Scale, Injury Severity Score, hospital length of stay, intensive care unit length of stay, and discharge status. Univariate and bivariate analyses were calculated. Statistical significance was P < .05.Results: One hundred fifty six patients met inclusion criteria. There were 120 (76.9%) female patients with a mean age of 34.5 years (range, 16 to 67 years). There were 36 (23%) male patients with a mean age of 43.8 years (range, 18 to 77 years). Women were statistically more likely than men to have government-subsidized insurance (47 [39.2%] vs 7 [19.4%]; P = .03), positive alcohol exposure (27 [22.5%] vs 19 [52.8%]; P = .0001), positive illicit drugs toxicology screen (25 [20.8%] vs 13 [36.1%]; P < .02), report physical abuse (24 [20%] vs 0; P = .004), have subarachnoid hemorrhage (14 [11.7%] vs 0; P = .04), and/or lower extremity injuries (39 [32.5%] vs 5 [13.9%]; P = .03).Conclusion: Males tend not to report physical abuse; this behavior contributes to IPV under-reporting in males.